ПОТОЦЬКІ ñ ВОЛОДАРІ ТАЛЬНІВСЬКОГО МАЄТКУ (Zaporizhzhia Historical Review, 2021)
A man is an element of any form of sociality from the earliest community to the modern civil and political super system. That is why this view to the historical processes, society is inseparable from studying of some persons and families. The article deals with the Pototskyís family and its contribution into the Ukrainian history and culture.